2013
DOI: 10.1002/stc.1598
|View full text |Cite
|
Sign up to set email alerts
|

Experimental studies on seismic performance of three-storey steel moment resisting frame model with scissor-jack-magnetorheological damper energy dissipation systems

Abstract: SUMMARY The supplemental passive and semi‐active dampers such as viscous fluid dampers, magnetorheological (MR) dampers are increasingly used to provide enhanced seismic protection of structures. A three‐storey quarter length scale steel moment resisting frame (SMRF) model, fitted with two scissor‐jack‐MR damper systems placed at ground floor level, is designed and fabricated to study its seismic response characteristics. The effective damping of the frame model for different input currents to MR dampers are f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 9 publications
(22 reference statements)
0
7
0
Order By: Relevance
“…Rama Raju et al . have tested a three‐storey quarter‐length‐scale steel moment resisting frame with two scissor‐jack‐MR damper systems placed at the ground floor. It was found that the scissor‐jack‐MR damper systems are effective in improving the performance of the building.…”
Section: Effective Damper Locationsmentioning
confidence: 99%
“…Rama Raju et al . have tested a three‐storey quarter‐length‐scale steel moment resisting frame with two scissor‐jack‐MR damper systems placed at the ground floor. It was found that the scissor‐jack‐MR damper systems are effective in improving the performance of the building.…”
Section: Effective Damper Locationsmentioning
confidence: 99%
“…The utilization of MRFs has been increasing in the different semi-active damping control applications in the low to moderate frequency ranges, including automotive suspension 28 , civil structures [29][30][31][32] , fluid clutches 33 , optical polishing 34 and a variety of aerospace applications [35][36][37][38] , vibration isolation 39,40 , automobile valves 41 and automotive damping applications 42 . Lord Corporation, the leading supplier of commercially proven MR fluids, devices and systems, manufactures three different MR fluids namely LORD MRF-122EG, LORD MRF-132DG and LORD MRF-140CG (ref.…”
Section: Studies On Mr Fluidsmentioning
confidence: 99%
“…MR dampers generally consist of a hydraulic cylinder containing micron-sized magnetically polarizable particles suspended within a fluid 31,32 . In the presence of strong magnetic field, the particles polarize and offer an increased resistance to flow.…”
Section: Application Of Mr Fluids -Mrfdmentioning
confidence: 99%
See 1 more Smart Citation
“…Chu et al proposed a leverage‐type stiffness controllable mass damper to resolve this problem. These practical examples have proved that, through the amplification mechanism, high values of the magnification factor can easily be achieved and a large amount of input seismic energy can be consumed. However, because of the differences in structural deformation and the space limitation, the brace–damper systems are less effective and appropriate for precast walls.…”
Section: Introductionmentioning
confidence: 96%